1996
DOI: 10.1055/s-0038-1650226
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Platelets in the Expression of Monocyte Tissue Factor Antigen Measured by a New Whole Blood Flow Cytometric Assay

Abstract: SummaryPrevious methods for the determination of monocyte tissue factor (TF) have been technically complex, difficult to standardize, prone to spuriously elevated results and difficult to implement in a clinical laboratory environment. We report the development of a two-color whole blood cytometric technique that overcomes many of these disadvantages. The assay uses small volumes of citrated blood (1.0 ml), can be performed in under one hour (if endotoxin stimulation is not performed), is reproducible (CV = 5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 0 publications
4
56
3
Order By: Relevance
“…Interestingly, no TF mRNA could be detected at the earliest time point of antigen detection. Early TF antigen induction by platelets in whole blood was observed by Amirkhosravi et al, 13 who also used 15-minute incubations for their collagen stimulation experiments. Similar observations have been made by other workers.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Interestingly, no TF mRNA could be detected at the earliest time point of antigen detection. Early TF antigen induction by platelets in whole blood was observed by Amirkhosravi et al, 13 who also used 15-minute incubations for their collagen stimulation experiments. Similar observations have been made by other workers.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent publication, Mach et al 19 showed reduction of atherosclerosis in mice by administration of anti-CD40L antibody. Platelets, known to activate leukocytes by P-selectin tethering, 13,20 are the most recent cell type to be found capable of CD40L expression. 8 In this study, we have investigated the role of CD40-CD40L interaction in activated platelet-induced TF expression in monocytic cells, both in a cell line and in a wholeblood environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of tissue factor HuMab (TF-011, TF-013, and TF-098) on whole-blood coagulation was assessed by TEG. Citrated whole blood, obtained from healthy donors, was incubated with LPS to induce tissue factor expression on monocytes and release of monocyte-derived tissue factorpositive microparticles (8,28). LPS treatment induced a decrease in clotting lag time compared with untreated blood (Supplementary Table S3), which, in this system, represents a measure for tissue factor activity.…”
Section: Tissue Factor Humab Show Minor Interference With Fxa Generatmentioning
confidence: 99%
“…Under physiologic conditions, tissue factor expression is mostly restricted to the cells of the subendothelial vessel wall, such as smooth muscle cells, pericytes, and fibroblasts, that are not in direct contact with the blood (6). In healthy individuals, blood leukocytes do not express tissue factor on the cell surface, although tissue factor expression has been described on 1% to 2% of monocytes (7,8). Activation of the coagulation cascade occurs when membrane-bound tissue factor is exposed to circulating FVII (a), for example, after disruption of the vessel wall by injury or after upregulation of tissue factor on monocytes under inflammatory conditions (9).…”
Section: Introductionmentioning
confidence: 99%